2021
DOI: 10.1159/000515004
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Dynamics in the Prefrontal Cortex during a Working Memory Task in Young Adult Smokers

Abstract: <b><i>Introduction:</i></b> Cigarette smoking is known to modulate brain metabolism and brain function. How the dynamics of these metabolic alterations influence the active performance of higher order cognitive tasks in smokers, compared to non-smokers, is still unclear. The present exploratory study sought to examine the impact of smoking on the “complete” metabolic profile while the participants performed a working memory (N-back) task. <b><i>Methods:</i></b> T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 49 publications
2
5
0
Order By: Relevance
“…Asp levels can induce severe neuroinflammatory processes and cell death (Boccella et al, 2015;Nuzzo, Feligioni, et al, 2019;Punzo et al, 2016). Our study found increased Asp levels in the mPFC of the brain of NAs, which we believe may be associated with the changes in the structure and cognitive functions of the mPFC as well as the addictive behavior (Bagga et al, 2021;Janes et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Asp levels can induce severe neuroinflammatory processes and cell death (Boccella et al, 2015;Nuzzo, Feligioni, et al, 2019;Punzo et al, 2016). Our study found increased Asp levels in the mPFC of the brain of NAs, which we believe may be associated with the changes in the structure and cognitive functions of the mPFC as well as the addictive behavior (Bagga et al, 2021;Janes et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Our study not only found elevated levels of Asp in the prefrontal lobe of the brain in NAs, but also found that Asp was associated with daily nicotine intake in the correlation analysis. Therefore, we think that nicotine should be clearly In addition, the differences between the NAs and nonsmokers are not caused by one metabolite, but may also be caused by interactions between metabolites (Bagga et al, 2021;. Most previous studies have shown that NAA, Cr, mI, and Glu in the brain of NAs are significantly decreased, while Cho is significantly increased (Durazzo et al, 2016;Gallinat et al, 2007;Mennecke et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations